ANALISIS PENGARUH TUNJANGAN KINERJA, PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DEPUTI BIDANG REHABILITASI DAN REKONSTRUKSI, BADAN NASIONAL PENANGGULANGAN BENCANA - Ramad Yuliarto (LPPM Politeknik Pratama, 2023)
This research was conducted at the Deputy for Rehabilitation and Reconstruction, National Disaster Management Agency. This research aims to examine and analyze the influence of performance allowance, training and work motivation on employee performance at the Deputy for Rehabilitation and Reconstruction, National Disaster Management Authority. t statistic value for performance allowances is 2.026 > t table 1.997, so the conclusion is that performance allowances have an effect on improving employee performance. t statistic value for training is 1.059 < t table 1.997, the conclusion is that training has no effect on improving employee performance. t statistic value for work motivation is 5.240 > t table 1.997, so the conclusion is that work motivation has an effect on increasing employee performance. F statistic value is 24.050 > F table 2.742, the conclusion is performance benefits, training and work motivation simultaneously (together) have an effect on improving employee performance, these three variables can be used to predict employee performance. R Square (coefficient of determination) is 0.522, this condition shows that the effect of performance allowances, training and work motivation in improving employee performance is 52.2 percent, the remaining 47.8 percent is influenced by other factors not tested in this research.